2020
DOI: 10.3390/brainsci10080478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Electrical Stimulation (NMES) Plus Upper Cervical Spine Mobilization on Forward Head Posture and Swallowing Function in Stroke Patients with Dysphagia

Abstract: After a stroke, forward head posture occurs, resulting in swallowing dysfunction. Neuromuscular electrical stimulation (NMES) combined with upper cervical spine mobilization has demonstrated enhanced recovery of the swallowing function in stroke patients. This study investigated the therapeutic effects of NMES in conjunction with upper cervical mobilization in stroke patients with dysphagia. Thirty-four stroke patients were recruited (in a randomized controlled clinical trial) and divided into an experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…bilitative interventions, combined compensatory and rehabilitative interventions, and no dysphagia intervention. Seventeen studies were excluded from meta-analyses: one study included patients with self-reported swallowing difficulties without confirmed OD diagnosis by instrumental assessment (VFSS or FEES) [48], four studies did not report on instrumental or clinical non-instrumental outcome data [20,28,37,40], ten studies provided insufficient data for meta-analysis [21,24,27,34,38,39,48,51,56,57], and two studies were excluded to reduce heterogeneity between studies [32,53].…”
Section: Meta-analysis: Effect Of Interventionsmentioning
confidence: 99%
“…bilitative interventions, combined compensatory and rehabilitative interventions, and no dysphagia intervention. Seventeen studies were excluded from meta-analyses: one study included patients with self-reported swallowing difficulties without confirmed OD diagnosis by instrumental assessment (VFSS or FEES) [48], four studies did not report on instrumental or clinical non-instrumental outcome data [20,28,37,40], ten studies provided insufficient data for meta-analysis [21,24,27,34,38,39,48,51,56,57], and two studies were excluded to reduce heterogeneity between studies [32,53].…”
Section: Meta-analysis: Effect Of Interventionsmentioning
confidence: 99%
“…We used G*Power 3.19 (Heinrich Heine University, Dusseldorf, Germany) for sample size calculations (Faul et al, 2009). Prior to commencing the investigation, we attempted to determine the sample size using the CVA (◦) average findings from the Jeon et al (2020) study. We calculated the total estimated required sample size for sufficient statistical power to be 20 (10 in the EG group, 10 in the control group), based on an assumed effect size of 1.443 (Jeon et al, 2020), statistical power of .80, and error probability of .05.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to commencing the investigation, we attempted to determine the sample size using the CVA (•) average findings from the Jeon et al ( 2020) study. We calculated the total estimated required sample size for sufficient statistical power to be 20 (10 in the EG group, 10 in the control group), based on an assumed effect size of 1.443 (Jeon et al, 2020), statistical power of .80, and error probability of .05. We recruited a conveninence sample of 24 volunteers with a history of stroke who were receiving follow-up care in the Department of Neurological Rehabilitation at Pamukkale University, Denizli/Türkiye.…”
Section: Participantsmentioning
confidence: 99%
“…The mobilization of the spinal joint, also known as the passive movement of the joint, is used to get the joint into the proper position with proper alignment and to increase the range of motion. Joint mobilization has the effect of inducing a reflex by stimulating articular receptors 17 . Meanwhile, the stabilization exercise provided stretching of the tight muscles and increasing the strength of weakened muscles so that the scapula muscles can be brought closer to the normal position 18 .…”
Section: Sling-based Manual Therapy and Stabilization Exercisementioning
confidence: 99%